CORRELATION OF CLINICAL INSTRUCTORS’ CHARACTERISTICS TO STUDENTS’ CLINICAL SKILLS SCORE IN A MIDWIFERY SCHOOL - Ika Friscila; Achadiyani Achadiyani; Endang Sutedja (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2020)
Background: The role of the clinical instructor is very important in clinical learning process that preparing students to become health workers who are competent in the practical environment. Effective clinical instructor is instructor who has profesional competence, interpersonal relationships, personality characteristics, and teaching skills in the process of providing guidance. The aim of the study was to analyze the relationship between clinical instructor characteristics and the score of pregnancy care clinical skills and analyze the most influenced characteristics of clinical instructor in the score of pregnancy care clinical skills in students of the Akademi Kebidanan Sari Mulia in Banjarmasin City.Methods: This study used a cross-sectional design with 11 clinical instructors and 25 Sari Mulia Midwifery Academy students using total sampling. This study used a Nursing Effectiveness Clinical Teacher Inventory questionnaire (NCTEI) questionnaire as instrument.Results: There is a relationship between clinical instructor characteristics and the score of pregnancy care clinical skills in students, namely interpersonal relationships (p = 0.043) and personality characteristics (p = 0.024). The dominant factor associated was personality characteristics (POR = 4.4; IK 95%: 1.02-19.08) with a value of p = 0.048.Conclusion: From this study, it can be concluded that the interpersonal relationships and personality characteristics can enhance the role of clinical instructor in the clinical learning process and personality characteristics represent the clinical instructor characteristics that are most in line with the score of pregnancy care clinical skills.